Carrying capacity in Danube's Delta: Link between local economy development and environmental resources protection - Ruxandra-Eugenia Pop (Agrarian Economy and Rural Development - Trends and Challenges. International Symposium. 13th Edition, 2022)
During COASTAL project, financed through Horizon 2020 program, research team carried out a modelling activity, for the three main economic activities for Danube's Delta study case area: agriculture, aquaculture and tourism. Regarding the tourism in Danube's Delta region, we wanted to find the answer to the following question: How far can be developed Danube's Delta area without damaging the environment?To achieve one of the main objective of modelling activity, several parameters with which the model operates where used, such as carrying capacity, variable of interest both for generating income within the tourist activity and to ensure the sustainability of the area from environment perspective. Therefore, Carrying capacity represent the central theme of this paper and we used different approaches from a conceptual, mathematical and logical point of view. Also, we presented elements of tourist demand and supply in the Danube Delta, in order to be able to compare the currently existing carrying capacity of the study case area with the hypothetical value, calculated among this paper.
Keywords: O13; Q18; 330; Danube's Delta; tourism; carrying capacity; rural development; tourism marketing